Genomic study of Rickettsia akari by pulsed-field gel electrophoresis. - Eremeeva, M (1995)
Pulsed-field gel electrophoresis of SmaI-, EagI-, and BssHII-digested DNA was used to perform restriction fragment length polymorphism analysis of Rickettsia akari strains isolated from humans, rodents, and mites in the United States and Ukraine. Although some differences in biological and serological characteristics were present between strains, the genomic studies demonstrated a high degree of intraspecies homogeneity of R. akari isolates. Our results confirm the value of pulsed-field gel electrophoresis-restriction fragment length polymorphism analysis for the identification of species of rickettsiae.